Ressecção laparoscópica do segmento lateral esquerdo do fígado em doador para transplante hepático inter-vivos - Coelho,Julio Cezar Uili (2009)
Laparoscopic resection of the left lateral segment of the liver in donors of living liver transplantation. The authors present a case of laparoscopic resection of the left lateral segment of the liver in a donor of living liver transplantation. The procedure was done in six hours and the left lateral segment of the liver was removed through a 15 cm right subcostal incision. The patient was discharged on the 5th post-operative day. A 40 mL intrabdominal collection of bile was percutaneously drained guided by ultra-sonography. The drain was removed after five days. Afterwards, the patient had good recovery with no other complication.